Molecular Farming in Artemisia annua, a Promising Approach to Improve Anti-malarial Drug Production - Pulice, Giuseppe; Pelaz, Soraya; Matías-Hernández, Luis (Frontiers in Plant Science, 2016)
Malaria is a parasite infection affecting millions of people worldwide. Even though progresses in prevention and treatment have been developed, 198 million cases of malaria occurred in 2013, resulting in 584000 estimated deaths. 90% of all malaria deaths occurred in Africa, mostly among children under the age of five. This article aims to review malaria’s history, epidemiology and current treatments, with a particular focus on the potential of molecular farming that use metabolic engineering in plants as effective anti-malarial solution. Malaria indeed represents an example of how a health problem on one hand, may eventually influence the proper development of a country due to the burden of the disease, and on the other hand, constitutes an opportunity for lucrative business of diverse stakeholders. In contrast, plant biofarming is here proposed as a sustainable alternative for the production not only of natural herbal repellents used for malaria prevention but also for the production of sustainable anti-malarial drugs like artemisinin used for primary parasite infection treatments. Artemisinin, a sesquiterpene lactone, is a natural anti-malarial compound that can be found in Artemisia annua plant. However, the low concentration of artemisinin in plant makes this molecule relatively expensive and difficult to meet the worldwide demand of Artemisinin Combination Therapies, especially for economically disadvantaged people in developing countries. The biosynthetic pathway of artemisinin, a process that only takes place in glandular secretory trichomes of A. annua, is relatively well elucidated, and significant efforts using plant genetic engineering have been made to increase the production of this compound. These include studies on diverse transcription factors, which all have been shown to regulate artemisinin genetic pathway and other biological processes. Therefore, genetic manipulation of these genes may be used as a cost-effective potential way for the synthesis and production of medicines against the malaria parasite. Finally, this article will also discuss two risks factors that already affect the fight against malaria. In first place, the onset and progressive development of anti-malarial drug resistance; secondly, the potential and underestimated impact of migrations and global climate changes on the spread of the disease in currently malaria-free countries.